Evaluation of Intraocular Lens Tilt and Decentration after Yamane Scleral Fixation and Their Influence on Residual Astigmatism - Truong Khah Van, Tham; Trung Hai Long, Nguyen; Thi Van Anh, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 2, 2026)
Abstract: Objective: To evaluate intraocular lens (IOL) tilt and decentration after Yamane scleral fixation and determine their influence on postoperative ocular residual astigmatism (ORA). Methods: A case series of 21 eyes undergoing Yamane fixation at the Vietnam National Eyes Hospital from February to September 2025 was analyzed. Ultrasound biomicroscopy (UBM) was used to measure IOL tilt and decentration along horizontal and vertical axes. Patients were categorized into well-positioned and malpositioned IOL groups. Visual acuity, refraction and ORA were assessed and correlated with IOL positioning. Results: Malpositioned IOLs were observed in 71.43% of eyes. Mean horizontal and vertical tilt were 3.47 2.31° and 4.77 4.07°; mean horizontal and vertical decentration were 0.83 0.64 mm and 0.38 0.71 mm. No significant difference was found in visual acuity between the two groups (P>0.05). Horizontal decentration showed a strong correlation with ORA (R=0.593; P=0.005), with the regression model: ORA=0.7926+1.2441x(horizontal decentration). IOL tilt demonstrated only a weak correlation with total astigmatism. Conclusion: Horizontal IOL decentration is the primary factor contributing to increased postoperative ORA following Yamane fixation. IOL tilt has a lesser impact. Precise control of IOL positioning is crucial to optimizing refractive outcomes. Keywords: Intraocular lens, Yamane technique, scleral fixation, IOL tilt, IOL decentration, ocular residual astigmatism.